Quantifying the economic benefits of payments modernization: The case of the large-value payment system - Neville Arjani; Fuchun Li; Zhentong Lu (Bank of Canada, 2021)
In this paper, we develop a discrete choice framework to quantify the economic benefits of payments modernization in Canada. Focusing on Canada's large-value transfer system (LVTS), we first estimate participants' preferences for liquidity cost, payment safety and the network effect by exploiting intraday variations in the relative choice probabilities of the two substitutable sub-systems in the LVTS (i.e., Tranches 1 and 2). Then, with the estimated model, we conduct counterfactual simulations to calculate the changes in participants' welfare when the LVTS is replaced by a real-time gross settlement system (RTGS), like Lynx (as an important part of the payments modernization initiative). The results show that, first, compared to the old system, Lynx has higher liquidity costs but is more secure, while the former is considered a more important factor by system participants. Second, when over 90% of current LVTS payments migrate to Lynx, there is an overall welfare gain; however, it maybe difficult to achieve such a high migration ratio in the new market equilibrium. Third, accounting for equilibrium adjustment, about a 75% service level improvement is needed to generate overall net economic benefits to participants. Among other things, adopting a liquidity savings mechanism and reducing risks in the new system could help achieve this improvement. Finally, the welfare changes are quite heterogeneous, especially between large and small participants.
Keywords: C3; E4; E42; G1; G2; G28; 330; Financial institutions; Financial system regulation and policies; Payment clearing andsettlement systems